Investigation of Thermal and Sound Insulation Properties of Sapwood and Heartwood of Willow Tree - Musa Kaya; Ramazan Bülbül; Mutlu Türk (BioResources)
The heat and sound insulation properties of the heartwood and sapwood of willow (Salix alba L.) were investigated.  Based on the experimental results, it was determined that the density value of the heartwood of the willow tree was higher than that of sapwood, while the moisture value was lower in the sapwood. The thermal conductivity coefficient was 0.090 W/m.K in sapwood and 0.103 W/m.K in heartwood; thermal transmittance coefficient was 3.954 W/m².K in sapwood and 4.738 W/m2.K in heartwood. The sound absorption coefficient was highest in sapwood at 1000 Hz frequency level with 0.37, while the highest in heartwood was 0.50 at 800 Hz frequency level. These results would be useful in willow wood structural applications.